Depressive symptoms in HIV-infected and seronegative control subjects in Cameroon: Effect of age, education and gender - Kanmogne, Georgette D. (PLoS One, 2017)
Depression is a leading cause of HIV/AIDS disease burden; it worsens health outcomes and quality of life. Addressing this problem requires accurate quantification of the extra burden of depression to HIV/AIDS in a given population, and knowledge of the baseline depression prevalence in the general population. There has been no previous study of depression in the general Cameroonian population. The current study attempts to address that important need. We used the Beck Depression Inventory-II to assess the prevalence and severity of depressive symptoms in 270 HIV-infected and seronegative Cameroonians. Univariate analyses showed a trend toward higher depressive symptoms among cases, compared to controls (p = 0.055), and among older subjects (>40 years), compared to younger subjects (≤40 years) (p = 0.059). Analysis of depression severity showed that 33.73% of cases had moderate-to-severe depressive symptoms, compared to 19.8% of controls (p<0.01). However, multivariable negative binomial regression analyses showed no effect of age, HIV status, CD4 levels, viral loads, ART, or opportunistic infections on the risk of depressive symptoms. Both univariate and multivariable regression analyses showed significantly higher risk of depressive symptoms among females compared to males; this was significant for both female controls and female cases. Female cases had significantly higher CD4 cell counts and lower viral loads, compared to males. Both univariate and multivariable regression analyses showed that lower education (≤10 years) was associated with increased risk of depressive symptoms. This study shows a high prevalence of depressive symptoms among seronegative controls and HIV-infected Cameroonians. Integrating care for mental disorders such as depression into primary health care and existing HIV/AIDS treatment programs in Cameroon may improve the wellbeing of the general population and could lower the HIV/AIDS burden.